New records of scleractinian coral in the Philippines: Euphyllia paraglabrescens - Luzon, Katrina S. (Animo Repository, 2001)
Euphyllia paraglabrescens Veron, 1990, is one of the eight Euphyllia species and one of the 14 members of the Family Euphyllidae. Veron (2000) reports Tanegashima, Japan as the exclusive biogeographic range of the species and his latest inventory of Philippine corals (Veron and Fenner 2000) did not list its occurrence here. Moreover, it is uncommon in the inshore reefs of Talim Bay, Lian, Batangas, and hence the species is hereby described.